A Simple Method for the Repair of Frontal Sinus Fracture: The Bone Mesh Pull-Up Technique. Issue 1 (March 2014) - Robiony, Massimo; Della Pietra, Lorenzo; Bertossi, Dario; Albanese, Massimo; Fresku, Arsa
Accurate reduction and stable fixation are important in the treatment of frontal sinus fracture. In this article, we introduce a rapid and simple method for the treatment of frontal fractures and restoration of normal forehead contour, named the "bone mesh pull-up technique" (BMPUT). We describe our experience with this technique in frontal trauma cases, with emphasis on the technical aspects and clinical results of this simple method. Postoperative computed tomography scans showed adequate reduction of displaced bone fragments in all cases. Esthetic results were satisfactory and no complications related to this procedure, such as uncontrollable sinus bleeding, infection, and posterior table and brain injuries, were observed. Follow-ups ranged from 1 to 24 months, with an average of 12 months. Contour deformities were effectively restored and cosmetic results were very good. The BMPUT is a safe procedure that can be performed with minimal morbidity and offers, good access, and excellent esthetic results.